Sustainability in German town and country planning law - Beaucamp, Guy (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
In 1998 the concept of sustainable development has become part of the federal town and country planning law. Beginning with a brief sketch of the sustainability concept, the article then examines which elements have been transferred into the legal text. Additionally their legal impact and the important role of regional planning are analysed.
Keywords: Article